2018
DOI: 10.13057/biodiv/d190224
|View full text |Cite
|
Sign up to set email alerts
|

Forest and land fires in Pelalawan District, Riau, Indonesia: Drivers, pressures, impacts and responses

Abstract: Tata HL, Narendra BH, Mawazin. 2018. Forest and land fires in Pelalawan District, Riau, Indonesia: Drivers, pressures, impacts and responses. Biodiversitas 19: 494-501. Pelalawan District of Riau Province, Indonesia was one of the districts most damaged by fire in 2015. Analysis of factors driving the fires, of pressures arising from the fires and of responses to the fires in Pelalawan District was conducted using two approaches: semi-structured interviews regarding social and policy aspects, and analysis of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Syaufina and Hafni (2018) stated that climate is one of the natural factors that can cause forest and land fires because climatic conditions can affect the level of surface fuel dryness, the amount of oxygen available and the speed at which the fire spreads. A study by Tata et al (2018) in Riau Province found a similar pattern that hotspots increased in number from June to August.…”
Section: Discussionmentioning
confidence: 64%
“…Syaufina and Hafni (2018) stated that climate is one of the natural factors that can cause forest and land fires because climatic conditions can affect the level of surface fuel dryness, the amount of oxygen available and the speed at which the fire spreads. A study by Tata et al (2018) in Riau Province found a similar pattern that hotspots increased in number from June to August.…”
Section: Discussionmentioning
confidence: 64%
“…In 2019, forest fires and land degradation emerged as a global issue [1]. Indonesia has been grappling with persistent forest and land fires for an extended period [2]. Forest and land fires are a recurring phenomenon in Indonesia, posing significant harm to the environment and human well-being almost annually [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of forest fires, such as haze were felt not only in Riau, but also in other provinces and even neighboring country such as Malaysia and Singapore. Forest fires' losses also impacted in multiple sectors, including economy [1], [3], public health, livelihood, and land degradation [4]. It is essential to detect and predict the occurrence of forest fires for prevention.…”
Section: Introductionmentioning
confidence: 99%